Antireflux mucosectomy for managing reflux symptoms in an obese patient post laparoscopic sleeve gastrectomy. (2nd December 2019) - Patil, Gaurav; Iyer, Arun; Dalal, Ankit; Maydeo, Amit
Abstract: Laparoscopic sleeve gastrectomy (LSG) is an effective treatment modality for obesity. Commonest delayed complication post LSG is gastroesophageal reflux disease (GER). The prevalence of GER among obese patients is higher than normal individuals. Such patients need long term Proton pump inhibitors (PPI) or antireflux procedures to manage reflux. Antireflux mucosectomy (ARMS) uses techniques of endoscopic mucosal resection to treat reflux for PPI refractory GER. However, it can be technically challenging to perform ARMS with a restricted stomach in patients who have undergone LSG. A 40-year-old female, hypertensive who had previously undergone LSG was treated for GER by a multidimensional approach with ARMS utilizing hypotensive anesthesia. The patient underwent the procedure successfully without any complication. She was discharged and at follow up visit, her reflux symptoms had improved and endoscopy was unremarkable. We describe this unusual case which was treated effectively with ARMS.